Efficacy of ceftazidime in a murine model following a lethal aerosol exposure to Burkholderia pseudomallei - Denise A. Pfefferle; Michael Hackett; Michael S. Anderson; Seth Gibbs; Lisa N. Henning; April C. Joice; Gabriel T. Meister (Scientific Reports, 2023)
Abstract Melioidosis is an endemic disease in numerous tropical regions. Additionally, the bacterium that causes melioidosis, Burkholderia pseudomallei, has potential to be used as a biological weapon. Therefore, development of effective and affordable medical countermeasures to serve regions affected by the disease and to have medical countermeasures available in the event of a bioterrorism attack remains critical. The current study evaluated the efficacy of eight distinct acute phase ceftazidime treatment regimens administered therapeutically in the murine model. At the conclusion of the treatment period, survival rates were significantly greater in several of the treated groups when compared to the control group. Pharmacokinetics of a single dose of ceftazidime were examined at 150 mg/kg, 300 mg/kg, and 600 mg/kg and were compared to an intravenous clinical dose administered at 2000 mg every eight hours. The clinical dose has an estimated 100% fT > 4*MIC which exceeded the highest murine dose of 300 mg/kg every six hours at 87.2% fT > 4*MIC. Based upon survival at the end of the treatment regimen and supplemented by pharmacokinetic modeling, a daily dose of 1200 mg/kg of ceftazidime, administered every 6 h at 300 mg/kg, provides protection in the acute phase of inhalation melioidosis in the murine model.